2004
DOI: 10.1248/cpb.52.488
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Simple Preparation Method of Matrix-Type Composite Particles for Controlled Drug Release by Mechanical Action

Abstract: Matrix-type composite particle for controlled drug release can readily be prepared through a totally dry process by simple anaerobic mechanical vibration of mechanoradical-containing ethylcellulose (EC) with theophylline powder due to occurrence of collision-induced radical-radical coupling reaction to form interparticle matrices, as well as the formation of interparticle network when solid-state vinyl monomer was further added.Key words matrix-type composite particle; controlled release; vibratory milling; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Cross-linking was observed upon mechanical milling of polyisoprene at cryogenic conditions by Spontak and co-workers . In the recycling of polymeric waste by shear pulverization, formation of mechanoradicals is probably a desired effect, which aids the in situ compatibilization of commingled plastic waste by formation of block and graft copolymers. , Mechanochemical solid-state polymerization was also used in prodrug syntheses by Kuzuya and co-workers. …”
Section: 14 Technological Relevance Of Polymer Mechanochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-linking was observed upon mechanical milling of polyisoprene at cryogenic conditions by Spontak and co-workers . In the recycling of polymeric waste by shear pulverization, formation of mechanoradicals is probably a desired effect, which aids the in situ compatibilization of commingled plastic waste by formation of block and graft copolymers. , Mechanochemical solid-state polymerization was also used in prodrug syntheses by Kuzuya and co-workers. …”
Section: 14 Technological Relevance Of Polymer Mechanochemistrymentioning
confidence: 99%
“…143,144 Mechanochemical solid-state polymerization was also used in prodrug syntheses by Kuzuya and coworkers. [145][146][147][148][149][150] Mechanochemistry is also employed in the development of biodegradable resins. Biodegradable soy protein-polyester blends have been prepared in a reactive extrusion process, using glycerol as a compatibilizing agent.…”
Section: Technological Relevance Of Polymer Mechanochemistrymentioning
confidence: 99%
“…From a plot of the square root of the microwave power vs. the signal peak height, a microwave power level of 0.01 mW was chosen. The procedure is essentially the same as that reported earlier [3][4][5][6]. Schematic representation is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 91%
“…[5,6] On the basis of a series of such studies, we here report the surface modification of low-substituted hydroxypropyl cellulose (L-HPC) powder, which is one of the widely used pharmaceutical excipients, by mechanochemical reaction of N-vinylacetamide (NVA) and plasmainduced radicals of L-HPC. Furthermore, when mechanical vibration of NVA and plasmairradiated L-HPC is similarly conducted with powdered drug, it can be expected that the drug is trapped among highly cross-linked powder particles resulted from mechanically-induced radical recombination.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] During the course of such studies on plasma-assisted DDS preparation, we have found that the carbon dioxide was trapped in the tablet when argon plasma was irradiated onto the DC tablet composed of plasma-crosslinkable polymers possessing carboxyl group as an outer layer. Since such tablets turned to floating system on the water, it was considered that this could be applicable to FDDS.…”
mentioning
confidence: 99%